Pengaruh Pembiayaan Natural Uncertainty Contract (NUC), Natural Certainty Contract (NCC), Dan Non Performing Finance (NPF) Terhadap Profitabilitas Bank Umum Syariah - Habibul Mubarok; Marliyah Suryadi; Rahmat Daim Harahap (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Profitability (ROA) is an important ratio in every company's financial statements. Profitability (ROA) reflects the ability to earn profits through funds invested in overall assets that produce profits. Profitability in a bank cannot be separated from the components in the financial reports such as total financing disbursed, financing problems faced by the bank, and so on. This research uses quantitative data based on secondary data obtained from quarterly financial reports. With all the profitability of Sharia Commercial Banks in Indonesia as the population and using purposive sampling as a sampling technique, the number of samples obtained in this research was 60 quarterly financial reports with an observation period of 20 quarterly financial reports for 5 years, for the period 2018- 2022 . The analytical method used in this research is multiple linear regression, R^2 test, t test and F test. The results of the study found that partially NUC financing had no positive effect on profitability (ROA), NCC financing had no negative effect on profitability (ROA). , and NPF have a significant negative effect on profitability (ROA). Simultaneously NUC, NCC, and NPF influence profitability (ROA).